TÜBİTAK 1MV Accelerator Mass Spectrometer Designed for 14C, 10Be, 26Al, 41Ca, 129I - Furkan Kulak; Erhan İlkmen; Turhan Doğan (Bulletin of the Mineral Research and Exploration, 2023)
A 1 MV Accelerator Mass Spectrometer (AMS) was established at TÜBİTAK, MRC Türkiye in December 2015. The 1MV TÜBİTAK AMS system is based on a Pelletron tandem accelerator, operating up to 1.1MV. Built by National Electrostatics Corporation (NEC), its design was unique at time of production. The TÜBİTAK 1MV AMS is based on the design of an XCAMS 0.5MV AMS also produced by NEC, but with a higher energy tandem accelerator. The higher energy accelerator features better precision (1% or less) for 10Be measurements. This new AMS also has larger magnets than the XCAMS. Larger magnets make it possible to measure 41Ca and 129I at the two-anode gasionization detector. In this article, the technical features; the parameters of ion source, terminal and other operations, and measurement quality are explained for accomplished performance of the five isotopic ratios, 14C/12C, 10Be/9Be, 26Al/27Al, 41Ca/40Ca, 129I/127I. This article also presents five years of data for 14C/12C ratio measurement quality control are represented as well.